Model Sekolah Berbasis Seni Budaya di Sekolah Dasar Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta - Dea Rakhimafa Wulandari (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The purpose of this study is to find out how the process of organizing a culture-based school and efforts to grow cultural values at Taman Muda Ibu Pawiyatan Tamansiswa Yogyakarta Elementary School. This study uses a qualitative approach with interview, observation and documentation. The technique of analysis data uses reduction data, data presentation and drawing conclusions. Based on the results of the study, it was obtained that the use of the school-based cultural arts model in Taman Muda Ibu Pawiyatan Tamansiswa Elementary School Yogyakarta Indonesia was motivated by arts education which was prioritized to build human character, cultivate self-reliant spirit and fertilize behaviour on the foundation of cultural values. The implementation of arts and culture-based schools is done by making culture a content that is packaged in local content subjects, namely dance, music, music and song, and Javanese language. While efforts to grow cultural values are carried out by cultivating cultural values through routine activities, spontaneous activities and also exemplary